Congenital Peripheral Vestibular Syndrome in a Domestic Ferret (Mustela putorius furo) - Moya, Alfonso (J Exot Pet Med, 2014)
A 3-month-old intact female ferret (Mustela putorius furo) was presented with a 2-month history of ataxia. On physical examination, the ferret had difficulty standing upright. During the neurologic examination, the patient had a left head tilt and positional strabismus, circled to the left, and was ataxic. Results of the complete blood count were consistent with a mild normocytic normochromic anemia. Initial treatment was supportive. Magnetic resonance imaging was performed and revealed an asymmetry of the inner ears. A brainstem auditory evoked response test was also performed. History, clinical signs, and diagnostic test results indicated that the ferret was suffering from congenital peripheral vestibular syndrome and left-sided deafness. Congenital disease should be considered in the differential diagnosis of young ferrets with peripheral vestibular syndrome. Supportive care and physiotherapy can improve balance and motor function, leading to an acceptable quality of life.